PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK-PAIR-SHARE (TPS) DISERTAI MEDIA TORSO TERHADAP HASIL BELAJAR IPA SISWA KELAS VIII MTsN KAYU KALEK KABUPATEN PESISIR SELATAN TAHUN PELAJARAN 2014/2015 - Yulianti, Resti - (STKIP PGRI Sumbar, 2014)
The students Biology learning achievement in class VIII of MTsN Kayu Kalek Kabupaten Pesisir Selatan on the Movement System of Human Being was still below the Minimum Standard Score. This was caused by the studentsâ who were less active in the learning process, the teachers who were rarely used varied instructional media, and the learning process which was still teacher-centered. To overcome the problem, Think-Pair-Share cooperative learning model assisted with Torso media was applied. The purpose of this research was to see the effect of using Think-Pair-Share cooperatif learning model assisted with Torso media on the studens learning achievement in Natural Science in class VIII of MTsN Kayu Kalek Kabupaten Pesisir Selatan in Academic Year 2014/2015. This was an axperimental research which used Randomized Control-Group Posttest Only Design. The population of the research was all of studentsâ in class VIII of MTsN Kayu Kalek registered in Academic Year 2014/2015. By using purposive sampling technique, class VIII6 was chosan as the experimental group, and class VIII3 was taken as the control group. The instrument of the research was a multiple choice written test. The data gathered was analyzed by using t-test on the significance level 95% and Î±= 0,05. The result of t-test indicated that the value of tcalculated (3,45) was higher than ttable (1,67) indicating that the hypothesis was accepted. Based on this result, it was concluded that the use of Think-Pair-Share cooperative learning model assisted with Torso media could improve the studentsâ leraning achievement in Natural Science in class VIII of MTsN Kayu Kalek Kabupaten Pesisir Selatan in academic year 2014/2015.